Effect of Henna Leaves (Lawsonia inermis) Incorporated Fish Feed on Growth, Survival and Pigmentation of Guppy, Poecilia reticulata (Peters, 1859) - Mohammed, Imran; Kowsigan, Loganathan; Abishag, Muthu; Faizullah, Mohamed; Meeran, Mohamed; Kumar, Ranjith; Kalaiselvan, Pandi (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during April, 2024–June, 2024 at Aquaculture wet laboratory of Dr. MGR Fisheries College and Research Institute, Thalainayeru. This research sought to examine how incorporating powdered dried henna leaves (Lawsonia inermis) into fish food impacts the growth, survival and pigmentation of guppy. For the experimental trial, 120 male guppies were stocked in 8 tanks (30 fishes treatment-1 in duplicate). The fish were fed with four isonitrogenous diets (33% Crude Protein) with different concentrations of Henna incorporation: Control (0%), H1 (1%), H2 (2%), and H3 (3%) for 60 days. At the end of the experiment, fish samples were analysed for growth parameters, survival, and pigment accumulation. Compared to the control group, H3 exhibited significantly higher (p<0.05) growth indicators, including specific growth rate, net weight gain, and weight gain percentage. The survival rate was significantly greatest (p<0.05) in H2, followed by H3, H1, with lowest survival rate observed in control group. The tissue carotenoid concentration was significantly (p<0.05) highest in control group, followed by H2, H3 and was significantly (p<0.05) lowest in H1. Colour intensity assessment using image J software® revealed that red colour exhibited significant lower value (p<0.05) in H3 compared to other groups (control, H1 and H2), while the green and blue colours exhibited significant greater value (p<0.05) in the control compared to all treatment groups (H1, H2 and H3). The present study demonstrated that incorporating 3% dried leaf powder of Lawsonia inermis in guppy feed enhanced growth parameters while simultaneously reducing carotenoid content. However, 2% incorporation was found to improve the survival rate.